Niepewność przedstawienia. Od kamery obskury do współczesnej fotografii. Wydanie drugie rozszerzone - Michałowska, Marianna (Wydawnictwo Naukowe Wydziału Nauk Społecznych UAM, 2017)
The book Uncertainty of representation: from camera obscura to contemporary photography proposes a cultural interpretation of pinhole photography, a technique which was particularly popular at the turn of the 20th and 21st century. Why I became interested in this specific photographic genre? Nothing gets older more quickly than technology. Nevertheless, the object of the analysis presented in the book – pinhole photography was old (or ancient) already in the moment of its invention. Might this be a reason why pinhole photography even today does not seem to be out of date. This direct successor of camera obscura, due to its aesthetical values (David Brewster rated highly in pinhole images some pictorial effects as lack of sharpness, which made the image more poetical), became the part of art discourse in 19th century. The advent of modern era in art marginalized pinholes for some time, but in the late 20th century the sudden fascination with lensless images thrived again together with the cultural and artistic activities of artists and theoreticians, who saw in photography not a mimetic reproduction of reality, but an image full of symbolic meanings and self-referential reflection on the language of medium. Such interpretation let artists like Gottfried Jäger, Paolo Gioli and, last but not least, the author of a seminal book on pinhole photography Eric Renner, come back to the basis of technological history of modern vision. The great interest of both experienced artists and young adepts of photography was influenced by the number of pinhole exhibitions also in Poland (by authors, whose artworks are the objects of interpretation in this book, such as Wiktor Nowotka, Paweł Borkowski, Piotr Zabłocki, Magdalena Poprawska, Zbigniew Tomaszczuk, Piotr Wołyński, Marek Noniewicz, Katarzyna Majak, Jarosław Klupś, Georgia Krawiec, Paweł Kula, Stefan Wojnecki and others). Digital era brought new possibilities for pinhole and it is still a medium of communication which negotiates memories, creates feeling of closeness, or expresses longing for a distanced object of desire.
Nic nie starzeje się szybciej od technologii. Kiedy w 2003 roku składałam pierwszą wersję tej książki do druku, nie tylko technologiczne możliwości fotograficznej rejestracji były inne, także same fotografie (przede wszystkim ze względu na mobilność) miały inny zasięg. Od czasu publikacji Niepewności przedstawienia fotografia fotochemiczna niemal zanikła, powracając do stanu z czasów początku wynalazku – szlachetnej pasji i mody. Jednak już w momencie publikacji książki przedmiot mojego zainteresowania – fotografia otworkowa nie należała do nowinek technologicznych. Wręcz przeciwnie – była stara (czy wręcz „staroświecka”), a jak kiedyś zauważył Hermann Lübbe: to, co historyczne „starzeje się o wiele wolniej od tego, co mniej stare”. Dlatego też, być może, pinhole photography nie wydaje się nieaktualna. Co prawda, widoczna na przełomie wieków fascynacja tą techniką nieco przygasła, ale okazało się, że bezobiektywowa camera obscura odnalazła swoją niszę w polu mediów cyfrowych. Nośnik fotochemiczny i digitalny dają współczesnym użytkownikom równie interesujące możliwości dla wizualnych eksperymentów. Co ważniejsze, kulturowe znaczenia wiązane z fotografią się nie zmieniły. Nadal obraz fotograficzny jest dla fotografujących i fotografowanych sposobem komunikacji, za pomocą którego można mieć poczucie bliskości, wyrażać tęsknotę oddalenia, a także odnaleźć swoje miejsce w świecie realnych przedmiotów. Dlatego też, w mojej opinii, uznanie fotografii bezobiektywowej za model służący zrozumieniu relacji człowieka i technologii wizualnych nadal może być instruktywne.
Keywords: fotografia otworkowa; semiotyka C.S. Peirce; fenomenologia E. Husserl; dekonstrukcja Derrida; dekonstrukcja Derrida; reprezentacja